PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PERNAPASAN MANUSIA KELAS V SD INPRES KUANINO 3 - Sela Sania Talan; Jannes Bastian Selly; Kurniayu T.R.A Ratu (STKIP Subang, 2025)
This study, entitled The Effect of Guided Inquiry Learning Model on Students’ Learning Outcomes on the Human Respiratory System Material for Grade V Students of SD Inpres Kuanino 3, aims to analyze whether there is an effect of the guided inquiry learning model and the problem-based learning model on students’ learning outcomes in the human respiratory system material, as well as to examine whether there are differences in learning outcomes between students taught using the guided inquiry model and those taught using the problem-based learning model. This research employed a quantitative approach using an experimental method with a non-equivalent group design. The population and sample of this study consisted of all fifth-grade students of SD Inpres Kuanino 3, totaling 40 students. The data collection techniques used were documentation and tests in the form of pre-tests and post-tests. Hypothesis testing was carried out using the Paired Sample t-Test with the assistance of SPSS version 27 for Windows. The results of the study indicate that there were significant differences in students’ learning outcomes before and after the implementation of both learning models. In the guided inquiry learning model, the students’ average score increased from 38.25 on the pre-test to 83.25 on the post-test, with a significance value of 0.000 < 0.05, indicating a highly significant improvement in learning outcomes. Meanwhile, the problem-based learning model also improved students’ learning outcomes, with the average score increasing from 33.5 to 69.25, although the improvement was lower than that of the guided inquiry model. The comparison between the two models shows that the guided inquiry learning model is more effective than the problem-based learning model in improving students’ learning outcomes on the human respiratory system material.